Migration and Human Capital Formation : Theory and Evidence From the U.S. High School Movement - Ramcharan, Rodney (Washington, D.C. : International Monetary Fund, 2002)
In 1910, 12 percent of American 14-17 year olds were enrolled in high school; by 1930, enrollment had increased to 50 percent; enrollment in Britain was 12 percent in 1950. This paper argues that by increasing the skill premium, the massive inflows of European unskilled immigrants at the turn of the twentieth century engendered America's sharp rise in human capital investment. The increased enrollments raised the supply of schools, leading to continued schooling investment. Cross section evidence and a VAR analysis of the time series data support the hypothesized role of immigration in generating the high school movement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet